Willingness To Pay Generasi Muda Terhadap Sayuran Organik di Wilayah Bogor dan Tasikmalaya (Jurnal Agribisnis Indonesia, 2024)
The younger generation is the generation that has awareness of the environment and health. This generation tends to choose clean, organic, and natural foods. Organic vegetables are products with the highest consumption level among other organic agricultural products. Organic vegetables generally have a higher price, but are thought to provide more health benefits than non-organic vegetables. The research objectives are (1) to identify young generation’s perceptions of organic vegetables compared to non organic vegetables, (2) to estimate Willingness to Pay (WTP) value of organic vegetables, and (3) to analyze the factors that influence WTP. Data collection was carried out by distributing online questionnaires from late February to early May 2023. The number of respondents was 200 respondents spread across the Bogor and Tasikmalaya areas. Data analysis in this research includes factor analysis, Contingent Valuation Method (CVM), and binary logistic regression. The results showed (1) young Generation’s perceptions of organic vegetables included perceived quality of organic vegetable products, perceived benefits of organic vegetables for the environment, perceived trust in organic vegetables, and perceived benefits of organic vegetables for health. (2) Most of the respondents (86%) stated that they were willing to pay for organic vegetables at a higher price and Bogor's WTP value was lower than Tasikmalaya's WTP value. (3) Factors that have a significant effect on respondents' willingness to pay more are perceptions of trust in organic vegetables and perceptions of the benefits of organic vegetables for health.